2015
DOI: 10.5005/jp-journals-10024-1762
|View full text |Cite
|
Sign up to set email alerts
|

Smokeless Tobacco-associated Lesions: A Mobile Health Approach

Abstract: Aim: Globally, India accounts for the highest number of oral cancer cases. The survival rates are about 30% lower than those in developing countries. The main reason for these dismal figures is the late presentation of patients. In order to downstage oral cancer in such a scenario, screening and diagnosis at an early stage is warranted. A pragmatic approach is needed for an oral cancer screening program, hence a mobile health (mHealth) approach was used. In this approach, health workers were empowered with mob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
1
2
0
3
Order By: Relevance
“…Upon age wise comparison of prevalence of different tobacco related lesions, tobacco pouch keratosis was found to be significant amidst younger age group (<45 years), consistent with findings of Rani et al (2015), it becomes apparent after 5-10 years of tobacco habit initiation and regresses with habit cessatation. Among the elder age group (>45 years) smokers melanosis was more prevalent consistent with findings of Binti Shahroom et al (2020), it is clinically characterised by brown to black discolouration, leading to melanin deposition, resulting from heat of smoke and melanocytes stimulation [19,20] . In our study the use of smokeless tobacco revealed significant association of mucosal lesions like tobacco pouch keratosis and OSMF stage 3 similar findings were reported by Prashant et al( 2013) [2] and Sujatha et al (2015) [3] .…”
Section: Discussionsupporting
confidence: 78%
“…Upon age wise comparison of prevalence of different tobacco related lesions, tobacco pouch keratosis was found to be significant amidst younger age group (<45 years), consistent with findings of Rani et al (2015), it becomes apparent after 5-10 years of tobacco habit initiation and regresses with habit cessatation. Among the elder age group (>45 years) smokers melanosis was more prevalent consistent with findings of Binti Shahroom et al (2020), it is clinically characterised by brown to black discolouration, leading to melanin deposition, resulting from heat of smoke and melanocytes stimulation [19,20] . In our study the use of smokeless tobacco revealed significant association of mucosal lesions like tobacco pouch keratosis and OSMF stage 3 similar findings were reported by Prashant et al( 2013) [2] and Sujatha et al (2015) [3] .…”
Section: Discussionsupporting
confidence: 78%
“…Poi mapper mobile application empowered health workers with a decision-based algorithm based on the risk stratification of tobacco habits [ 43 ]. A group of factory employees ( n = 1357) with pure tobacco chewing habits were screened in two phases.…”
Section: Resultsmentioning
confidence: 99%
“…In the later phase, the remote diagnosis was established by an oral medicine specialist based on the clinical photographs. Seventy-one subjects required biopsy and the histopathology results of most cases showed hyperkeratosis and mild dysplasia, with one case of moderate dysplasia [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Estudos identificaram a possibilidade de outros profissionais de saúde da atenção primária serem treinados para atuar junto a um especialista, compartilhando informações ou os consultando remotamente, quando tratar-se de áreas onde não existam cirurgiões-dentistas disponíveis, fornecendo imagens de lesões e informações clínicas, buscando o rastreamento de doenças bucais e obtenção de orientações sobre encaminhamento (Birur et al, 2019;Desai et al, 2015;Perdoncini et al, 2021). O estabelecimento da teleodontologia pode ocorrer por meio de aplicativos móveis acessados através de smartphones, facilmente utilizados, exigindo menos treinamento e custos, tornando a ferramenta capaz de agregar melhorias à saúde pública, e, ainda que despesas com internet móvel estejam previstas, as reduções de gastos com deslocamento resulta em economia e garantem maior equidade na saúde, o que reforça a relação custo-benefício quando se compara a outros equipamentos mais sofisticados que exigem investimentos relevantes, como é o caso da teleconferência de alta resolução que utiliza fibra ótica e internet de alta velocidade, considerando que a população que mais necessitada da teleodontologia não teria acesso a esses equipamentos (Birur et al, 2019;Perdoncini et al, 2021;Ben-Omran et al, 2021;Vinayagamoorthy et al, 2019).…”
Section: Discussionunclassified
“…A abordagem remota tem capacidade, inclusive, de reduzir falhas do sistema presencial, através, por exemplo, da manutenção de dados eletrônicos, e a possibilidade de realizar o acompanhamento do paciente e das lesões ao longo do tempo. Em estudo realizado com idosos chilenos, a plataforma desenvolvida oportunizou ao cirurgião-dentista especialista acompanhar a aparência das lesões, documentando alterações de forma intuitiva, sendo todos os dados registrados e catalogados digitalmente, o que representa uma grande ajuda para intervenção clínica desses pacientes (Birur et al, 2019;Desai et al, 2015;Venegas et al, 2022).…”
Section: Discussionunclassified